Baroreceptor stimulation in a patient with preexisting subcutaneous implantable cardioverter defibrillator. Issue 1 (16th June 2017) - Weipert, Kay F.; Andrick, Jens; Chasan, Ritvan; Gemein, Christopher; Most, Astrid; Hamm, Christian W.; Erkapic, Damir; Schmitt, Joern
Abstract: Background: Many patients with severe heart failure (HF) have an indication for baroreflex activation therapy (BAT) and an implantable cardioverter‐defibrillator (ICD). Concerns about device‐device interactions were addressed in a study with small sample size that concluded combined BAT and ICD therapy is safe. There are no published data, however, concerning device‐device interactions between BAT and a subcutaneous ICD (S‐ICD). Since BAT frequently interferes with surface electrocardiogram recordings, there are doubts about compatibility of BAT and S‐ICD devices. Case Description: A 54‐year‐old male patient with dilated cardiomyopathy and severely reduced left ventricular ejection fraction received an S‐ICD after recurrent systemic infections due to a diabetic foot syndrome, ultimately associated with infective endocarditis. Since medical HF therapy could not be further optimized and the patient presented with persistent cardiac decompensations, he was evaluated for BAT. Preoperatively, the barostim was epicutaneously placed on the patient's thorax with conductive gel in order to evaluate a possible interference with the S‐ICD. Positioning of the barostim in loco typico did not affect the S‐ICD's sensing in any vector. Only positioning of the carotis sinus lead directly upon the S‐ICD lead, which is beyond clinical relevance, lead to missensing. Subsequently, BAT was implanted with successful perioperative testing of the S‐ICD: there was accurate detection of ventricular fibrillation and immediate termination via first shock delivery under maximum barostim output. Conclusions: To our knowledge, there are no other reports in which a barostim was safely implanted in a patient with a preexisting S‐ICD. Until data with large patient numbers are available, individual perioperative testing is highly recommended.